Conceptualización y análisis de los sistemas de seguimiento solar - Chacón-Pinzón, Enrique
SummaryThis document presents a conceptualizationabout the solar tracking system, the types of solartrackers that exist in the market, which advantagesand disadvantages has and compares thedifferent solar tracking systems based on testscarried out around the world. After following thisanalysis, we can conclude which is the type ofsolar tracker that best adapts to the differentneeds of each site. Likewise, a description of theconstruction of a prototype solar tracker is madewhere constructive aspects are shared with theappropriate conclusions based on research andexperimentation.